Comunicación en museos a través de redes sociales durante la pandemia: desvelando nuevas oportunidades de interacción - Victoria FERNÁNDEZ FERNÁNDEZ,Dr. Miguel Ángel SUÁREZ SUÁREZ,Dra. Roser CALAF MASACHS (Fonseca, Journal of Communication, 2023)
The evolution of New Information and Communication Technologies (NICT) has suggested changes in the museum’s communication with its visitors, promoting a multidirectional relationship between the users and museum using Social Media (RRSS) that allows avoiding the physical distance